Efforts to Improve Learning Motivation and Learning Outcomes Throw in the Game Softball through Traditional Games - Badawi, Ahmad; Kurniawan, Achmad Rudy; Setyawati, Heny (Universitas Pendidikan Ganesha, 2023)
Student motivation in participating in the learning process is very important so that learning objectives can be achieved in learning. This study tries to implement traditional games as a learning model that will stimulate students' motivation in participating in learning by applying games before entering the softball core material. This study aims to analyze the increase in learning outcomes and student motivation in learning physical education on softball material. The method used in this research is classroom action research. The subjects of this study were class X-1 who took part in physical education lessons on softball with a total of 36 students consisting of 17 male students and 19 female students. Methods of data collection by conducting and questionnaires. Data analysis techniques using quantitative and qualitative analysis. The learning process by applying traditional games has a positive impact on cycles 1 and 2 showing an increase in learning outcomes through traditional games showing an average value of 70 to 79.6, an increase of 9.1%. The presentation of increased student learning outcomes from the initial conditions to cycle 2, namely from an average value of 66.9 to 79.6, there was an increase of 12.7%. Meanwhile, traditional games increase students' learning motivation from enough to good category. From the results of the study showed that through traditional games can improve learning outcomes and motivation to learn physical education on the material throwing in the game softball.